Skipping Rope XI / Ilya Natasha Ibrahim - Ibrahim, Ilya Natasha (2020)
This report is dedicated to discussing Skipping rope's new product development which is the skipping rope or jumping rope is to help users to use two functions at the same time which is set timer while keeping count on his or her jumps simultaneously. Research and development phase were undertaken against product making due to providing a successful product to be sold on the market. A survey has been conducted and showed that 38.1% of the respondents are interested in using the product if the product is useful for their workouts. The survey also identified that the respondents prefer both heavy and light skipping rope. Also, they chose the weight based on their comfortability and definitely they need the product to be in the market. In addition, product technology is developed by conducting research and also asking for the opinion of electrical technicians and engineers to obtain the perfect material and the appropriate technology that suits the product. Through performing the survey, feedback received from the respondents to develop the product design and make it more appealing because the apps are compact and user-friendly. Moreover, a standard market testing was conducted to identify the accuracy of applying the product in the world and to identify the improvement that can be applied towards the product.